Elderly patients with community-acquired pneumonia: Optimal treatment strategies - Thiem, Ulrich; Heppner, Hans Jürgen; Pientka, Ludger (Drugs & Aging, 2011)
Community-acquired pneumonia (CAP) is a common infectious disease that still causes substantial morbidity and mortality. Elderly people are frequently affected, and several issues related to care of this condition in the elderly have to be considered. This article reviews current recommendations of guidelines with a special focus on aspects of the care of elderly patients with CAP.The most common pathogen in CAP is still Streptococcus pneumoniae, followed by other pathogens such as Haemophilus influenzae, Mycoplasma pneumoniae, Chlamydophila pneumoniae and Legionella species. Antimicrobial resistance is an increasing problem, especially with regard to macrolide-resistant S. pneumoniae and fluoroquinolone-resistant strains. With regard to β-lactam antibacterials, resistance by H. influenzae and Moraxella catarrhalis is important, as is the emergence of multidrug-resistant Staphylococcus aureus. The main management decisions should be guided by the severity of disease, which can be assessed by validated clinical risk scores such as CURB-65, a tool for measuring the severity of pneumonia based on assessment of confusion, serum urea, respiratory rate and blood pressure in patients aged ≥65 years.For the treatment of low-risk pneumonia, an aminopenicillin such as amoxicillin with or without a β-lactamase inhibitor is frequently recommended. Monotherapy with macrolides is also possible, although macrolide resistance is of concern. When predisposing factors for special pathogens are present, a β-lactam antibacterial combined with a β-lactamase inhibitor, or the combination of a β-lactam antibacterial, a β-lactamase inhibitor and a macrolide, may be warranted. If possible, patients who have undergone previous antibacterial therapy should receive drug classes not previously used.For hospitalized patients with non-severe pneumonia, a common recommendation is empirical antibacterial therapy with an aminopenicillin in combination with a β-lactamase inhibitor, or with fluoroquinolone monotherapy. With proven Legionella pneumonia, a combination of β-lactams with a fluoroquinolone or a macrolide is beneficial. In severe pneumonia, ureidopenicillins with β-lactamase inhibitors, broad-spectrum cephalosporins, macrolides and fluoroquinolones are used. A combination of a broad-spectrum β-lactam antibacterial (e.g. cefotaxime or ceftriaxone), piperacillintazobactam and a macrolide is mostly recommended. In patients with a predisposition for Pseudomonas aeruginosa, a combination of piperacillintazobactam, cefepime, imipenem or meropenem and levofloxacin or ciprofloxacin is frequently used. Treatment duration of more than 7 days is not generally recommended, except for proven infections with P. aeruginosa, for which 15 days of treatment appears to be appropriate. Further care issues in all hospitalized patients are timely administration of antibacterials, oxygen supply in case of hypoxaemia, and fluid management and dose adjustments according to kidney function.The management of elderly patients with CAP is a challenge. Shifts in antimicrobial resistance and the availability of new antibacterials will change future clinical practice. Studies investigating new methods to detect pathogens, determine the optimal antimicrobial regimen and clarify the duration of treatment may assist in further optimizing the management of elderly patients with CAP. © 2011 Adis Data Information BV. All rights reserved.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Antibacterials; Community-acquired-pneumonia; Elderly